Identity constructing at Facebook profiles of the presidential candidates - Svobodova, Jindriska (Bohemica Olomucensia, 2014)
The author's main focus in the presented paper was to explore communication strategies used by the presidential candidates in their pre-election campaigns run at their Facebook profiles. The efforts aimed to create a positive self-image of each politician and dishonour their political rivals have become a natural part of the political competition in the pre-election time. Thus the author's attention was driven towards the means used by politicians to negotiate their own positive face as well as the means used within communication acts threatening the face of their political competitors.